PENGELOLAAN PEMBELAJARAN TRANSFORMATIF DALAM MENINGKATKAN KREATIVITAS DAN INOVASI MAHASISWA DI STAIN SULTAN ABDURRAHMAN KEPULAUAN RIAU - Aini, Wirdatul (As-Sulthan Journal of Education, 2025)
This study aims to analyze the strategies, steps, and contributions of learning management in enhancing the creativity and innovation of students at STAIN Sultan Abdurrahman Kepulauan Riau. A qualitative research method with a descriptive approach was used, employing observation, interviews, and documentation for data collection. The findings indicate that transformative learning has been effectively implemented through planning, organizing, execution, and evaluation. Enhancing students' creativity and innovation is supported by appreciating new ideas, focusing on intrinsic motivation, encouraging critical thinking, and providing adequate time for exploration. Transformative learning significantly contributes by fostering critical, creative, and innovative thinking among students while also motivating lecturers to improve their teaching. Thus, transformative learning management plays a crucial role in enhancing students' academic quality.